THE IMPACT OF DOUBLE TAX TREATIES ON INWARD FDI IN ASEAN COUNTRIES - Dong, Yue (JBFEM, 2018)
This study aims to assess the impact of double taxation treaties (DTTs) on FDI inflows in 10 ASEAN countries from 1989 to 2016. There are two objectives of double taxation treaties. The first one is to alleviate the problem of global double taxation, which has a stimulating effect on FDI. The second objective is the sharing of information between governments, which can prevent tax evasion and thus discourage FDI. The findings suggest that new DTTs tend to have a positive but insignificant impact on the FDI inflows into Southeast Asia. However, the impact of older DTTs on FDI is significantly negative, suggesting that the increasing number of DTTs signed by ASEAN countries over time does not lead to more FDI inflows into the region. Overall, the results show that tax treaties have little or even negative effect on FDI inflows into the ASEAN region, which is consistent with most prior findings that DTTs’ impact on FDI into low-income countries is not significant. However, the negative association between DTT and FDI is unlikely to be due to the information-sharing function of tax treaties based on an examination of the exchange of information (EOI) provisions contained in the 430 DTTs signed by ASEAN countries. The author proposes that the negative impact of DTTs on FDI inflows in ASEAN could be driven by factors associated with the ‘age’ of some existing DTTs. For example, certain provisions in some older treaties may have become outdated or irrelevant, thus hindering investment flows into the region.